Setting the standard for project based learning a proven approach to rigorous classroom instruction - Larmer, John; Mergendoller, John R.; Boss, Suzie (ASCD, 2015)
Project based learning (PBL) is gaining renewed attention with the current focus on college and career readiness and the performance-based emphases of Common Core State Standards, but only high-quality versions can deliver the beneficial outcomes that schools want for their students. It's not enough to just "do projects." Today's projects need to be rigorous, engaging, and in-depth, and they need to have student voice and choice built in. Such projects require careful planning and pedagogical skill. The authors leaders at the respected Buck Institute for Education take readers through the step-by-step process of how to create, implement, and assess PBL using a classroom-tested framework. Also included are chapters for school leaders on implementing PBL systemwide and the use of PBL in informal settings.